Hydrothermally synthesized tungsten trioxide nanorods as NO2 gas sensors. Issue 3 (April 2015) - Patil, V.B.; Adhyapak, P.V.; Patil, P.S.; Suryavanshi, S.S.; Mulla, I.S.
Abstract: One-dimensional single-crystalline h-WO3 nanorods have been synthesized by using a facile hydrothermal technique. Crystal structure, morphology evolution and thermal stability of the products are characterized by using X-ray Diffraction pattern, Scanning Electron Micrographs, Photoluminescence reflectance spectrum; UV–vis diffused reflectance spectral analysis and Raman techniques. The evolution and distribution of WO3 nanorods strongly depend on hydrothermal reaction temperature and time of reaction. Hydrothermal reaction temperature of 170 °C for 48 h ensures the formation of well-defined agglomerated WO3 nanorods. Gas response measurements reveal that WO3 sensor operating at 250 °C exhibits highest sensitivity towards NO2 with low cross sensitivity towards LPG, acetone and ammonia gas, which makes this material a competitive candidate for NO2 sensing applications. A possible adsorption and reaction model is proposed to illustrate formation of one dimensional nanostructure and gas sensing mechanism.